MicroRNAs Targeting HIF-2α, VEGFR1 and/or VEGFR2 as Potential Predictive Biomarkers for VEGFR Tyrosine Kinase and HIF-2α Inhibitors in Metastatic Clear-Cell Renal Cell Carcinoma - Kinget, Lisa (Cancers (Basel), 2021)
SIMPLE SUMMARY: Metastatic clear-cell renal cell carcinoma is characterized by heightened angiogenesis through increased expression of HIF-2α and VEGFR2. VEGFR tyrosine kinase inhibitors are a cornerstone of metastatic clear-cell renal cell carcinoma treatment, and new treatments targeting HIF-2α are currently under investigation. However, clinically useful biomarkers that can predict response to these treatments are lacking. MicroRNAs are small RNA molecules that interfere with gene translation. In this study, we identified four microRNAs that potentially interfere with the translation of VEGFR1 and/or VEGFR2 and are associated with tumor shrinkage and progression-free survival upon treatment with VEGFR-TKIs. These microRNAs might be predictive of response to VEGFR-TKIs. Moreover, we identified three microRNAs associated with HIF-2α expression and with tumor shrinkage and progression-free survival upon treatment with VEGFR-TKIs. These three microRNAs might be able to predict response not only to treatment with VEGFR-TKIs but possibly also to treatment with the upcoming HIF-2α inhibitor belzutifan. ABSTRACT: Metastatic clear-cell renal cell carcinoma (m-ccRCC) is characterized by increased hypoxia-induced factor (HIF)-2α and vascular endothelial growth factor receptor (VEGFR)-dependent angiogenesis through loss of function of the von Hippel–Lindau protein. VEGFR tyrosine kinase inhibitors (VEGFR-TKIs) are a cornerstone of m-ccRCC treatment, and new treatments targeting HIF-2α are currently under investigation. However, predictive biomarkers for these treatments are lacking. In this retrospective cohort study including 109 patients treated with VEGFR-targeted therapies as first-line treatment, we aimed to study the possible predictive function of microRNAs (miRNAs) targeting HIF-2α, VEGFR1 and VEGFR2. We selected miRNAs inversely correlated with HIF-2α, VEGFR1 and/or VEGFR2 expression and with predicted target sites in the respective genes and subsequently studied their impact on therapeutic outcomes. We identified four miRNAs (miR-34c-5p, miR-221-3p, miR-222-3p and miR-3529-3p) inversely correlated with VEGFR1 and/or VEGFR2 expression and associated with tumor shrinkage and progression-free survival (PFS) upon treatment with VEGFR-TKIs, highlighting the potential predictive value of these miRNAs. Moreover, we identified three miRNAs (miR-185-5p, miR-223-3p and miR-3529-3p) inversely correlated with HIF-2α expression and associated with tumor shrinkage and PFS upon treatment with VEGFR-TKIs. These three miRNAs can have a predictive value not only upon treatment with VEGFR-TKIs but possibly also upon treatment with the upcoming HIF-2α inhibitor belzutifan.